Magnetic carbon nanotubes obtained from plastic as catalysts for wet peroxide oxidation of paracetamol - Sanches, Lucas Fenato (2021)
Magnetic carbon nanotubes (MCNTs) were prepared by catalytic chemical vapour deposition (CCVD) and tested as catalysts for catalytic wet peroxide oxidation (CWPO) of paracetamol (PCM). For the synthesis of the MCNTs, low-density polypropylene (LDPE) and high-density polypropylene (HDPE) were used as model carbon precursors present in urban plastic solid waste (Aboul-Enein, 2018). The catalyst employed in CCVD was magnetite supported on alumina prepared by a sol-gel process. The CWPO runs were conducted with the stoichiometric concentration of H2O2 needed for the full mineralization of 100 ppm of PCM, at 80 °C and initial pH 3.5, following experimental methods described elsewhere (Silva, 2019). The catalyst prepared from LDPE, LDPE_MCNTW, was able to completely degrade the pollutant within 6 h of reaction, while HDPE_MCNTW took 8 h to achieve the same removal. Iron measurement in the final reaction solutions showed the absence of possible additional pollution coming from iron leaching of the catalysts.